Proses Komunikasi Instruksional dalam Pembelajaran Vokasional - Thadi, Robeet (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
The purpose of this study was to see how the instructional communication process in vocational learning in SMK 1 Kota Bengkulu. This type of research is qualitative research with a tradition of symbolic interactionism. So, with this method the researcher obtains a description of the research based on the experience of the subject itself. Data collection techniques used were observation and in-depth interviews. The data analysis technique uses qualitative data analysis. The results of this study are instructional communication applied in teaching vocational students is verbal and non verbal communication. Verbal communication in the form of simple words. Non-verbal communication is carried out in the form of body movements. In addition, interpersonal communication was also found. Conclusion, the instructional communication process applied in teaching vocational students at SMKN 1 Kota Bengkulu is verbal and non verbal communication. Keywords: Instructional, Learning, Vocational Communication.